RANGE EXTENSIONS OF DIABOLICAL NIGHTJAR Eurostopodus diabolicus AND INDONESIAN SERIN Chrysocorythus estherae ON SULAWESI OF THE WALLACEA REGION - Mohammad Irham; Yong Chee Keita Sin; Sng Chen Xi; Yohanna; Tri Haryoko; Dewi M Prawiradilaga; Rauri C.K Bowie; Frank E Rheindt (Treubia, 2024)
Sulawesi is an important endemicity hotspot in Southeast Asia, with over 100 endemic species distributed on the island. Despite a long history of avian research on Sulawesi that has played a significant role in the development of evolutionary theory, many ornithological aspects remain unknown. The last few decades have seen novel discoveries, for example, in the form of new species range extensions and species discoveries in the face of ongoing habitat loss and conversion. We here report on a range extension and notes of morphological descriptions of the endemic Diabolical Nightjar and Indonesian Serin in Southeast Sulawesi, adding to our knowledge of the distribution of Sulawesi’s avifauna, especially in the southeastern part in which visits from ornithologists are less frequent. A review of recent museum collections adds another new locality for Diabolical Nightjar in South Sulawesi. Future taxonomic studies are needed to elucidate the status of both species, especially in the Indonesian Serin, as the subtle differences in the coloration of the forehead, rump, and upper tail covert may indicate more than one taxon exists in Sulawesi. In addition, we provide an annotated checklist of birds observed during the fieldwork encompassing areas around Kolaka and Makassar.